2021
DOI: 10.1051/e3sconf/202126404012
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties lime-ammonium nitrate based on chalk, nitrate and ammonium sulphate

Abstract: For the granulation of nitrate-sulfate-carbonate melt, the prilling method is applied using a granulation tower. The composition and properties of new types of fertilizers were studied. It is shown that with the ratio NH4NO3: СаСО3: (NH4)2SO4 = 100: 24: 1 the product contains 28,03% - N, 0,50% - SO3, 10% - СаО and has a granule strength of 6.03 MPa, which is much higher than the strength of pure NH4NO3 granules (1.32 MPa). The absorption of pure AN granules is 4.82 g. With an increase in the proportion of chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In the next stage of the work, the influence of the dispersed composition of ammonium sulfate on the strength of granules of sulfated urea was studied. It is known that the higher the strength of fertilizer granules, the longer the product is stored in a crumbly state, and it also affects the caking of the product [19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…In the next stage of the work, the influence of the dispersed composition of ammonium sulfate on the strength of granules of sulfated urea was studied. It is known that the higher the strength of fertilizer granules, the longer the product is stored in a crumbly state, and it also affects the caking of the product [19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Extensive agrochemical tests of ammophosphate have shown that in terms of efficiency it is not inferior to ammophos and double superphosphate and can be used in various soil and climatic zones for all agricultural crops [6].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal norm (60%) of sulfuric acid and the weight ratio of phosphorite to oxidized coal (1 : 0.25) were found. Highly efficient humic superphosphates have been obtained from all types of raw materials, even as poor as ordinary phosphate flour [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%